Effective maintenance management : risk and reliability strategies for optimizing performance - Narayan, V. (Industrial Press, 2012)
"This book describes the crucial role of maintenance in minimizing the risk of safety or environmental incidents, adverse publicity, and loss of profitability. And it explains the applicability of risk-reduction tools to specific situations, thereby enabling you to select the tool that best fits your requirements." -- Cover